Pedagogical Political Project: a look for inclusive education in the countryside - Tatiane Motta Da Costa e Silva; Rodrigo de Souza Balk; Mylena Francini da Rosa; Joana dos Santos da Silva Corbette (Universidade Federal do Norte do Tocantins, 2023)
The Pedagogical Political Project (PPP) is characterized by being the guiding document of pedagogical practice at school, carrying with it an intention and contributing to the creation of school identity. This study aims to identify the perspectives of inclusive education and rural education present in the PPPs of schools located in the countryside of the municipality of Uruguaiana, Rio Grande do Sul, Brazil. This is a study with a qualitative approach, characterized in terms of objectives as exploratory and descriptive and in terms of procedures as a documentary research. The research was developed in 10 schools located in the countryside, being 6 municipality and 4 state. As for the results, advances are observed, such as methodological and evaluative adaptations with a view to promoting inclusive education. However, the perspectives of rural education and rural schools still need more attention, as they are present in a minority of PPPs, evidencing the little visibility given to the theme. Finally, it is concluded that the PPP as a guiding document has the role of establishing and contemplating the specificities of the school community, enhancing the relationship between the school environment and the appreciation of the countryside, without imposing a standardized school educational method.